PENGARUH MODEL COOPERATIVE LEARNING TIPE THINK PAIR SHARE TERHADAP HASIL BELAJAR PKN DI SD - Rahmi, Ismika; Reinita, Reinita; Mahyuddin, Ritawati (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
Abstract                                         The purpose of this research was to know the influence of Cooperative Learning Model Think Pair Share (TPS) toward student learning outcomes in class V SDN 09 Belakang Balok Bukittinggi City. This type of research was quasi experiment with Design Nonequivalent Control Group Design. The population in this research was students of grade V SDN 09 Belakang Balok Bukittinggi City. Sampling technique was nonprobability sampling with jenuh sampling type. The instrument used in this research was a test. Data analysis technique in the form of hypothesis test using t-test formula. Result of hypothesis test calculation at significance level 5% obtained thitung  > ttabel  that is 2,53> 2,00758 which means Ha accepted, that is there is significant influence model Cooperative Learning type Think Pair Share (TPS) to Student Learning Outcomes in Class V SDN 09 Belakang Balok Bukittinggi City. Keywords: Think Pair Share, Learning Outcomes